PROSES PENYUSUNAN RANCANGAN PRODUK HUKUM JAWA BARAT YANG MENGATURKETENTUAN RETRIBUSI JASA PERIZINAN TERTENTU - Taufik Syawal Lesmana Ramdani; Novie Indrawati Sagita; Ufa Anita Afrilia (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Optimizing local own-source revenue is a crucial aspect in supporting regional development and public service delivery. One of the key instruments in this effort is the formulation of regulations governing regional levies, particularly Certain Licensing Service Retributions. This study analyzes the process of drafting the Governor Regulation at the Regional Revenue Agency (BAPENDA) of West Java Province, focusing on the formulation stages, inhibiting factors, and resolution strategies. The approach used includes field observation, interviews, and literature review of relevant policies and legislation. The analysis shows that the drafting process requires synchronization between regional and national policies, such as Law No. 1 of 2022 and Government Regulation No. 35 of 2023. Major obstacles include limited technical capacity and suboptimal cross-sectoral coordination. Innovation in the form of digital systems such as the Sipandu application contributes to improving efficiency and transparency in levy management. Recommendations are focused on enhancing the competency of officials in regulation drafting and strengthening inter-agency coordination to ensure a more effective and targeted policy formulation process.